(untitled) (JURNAL KEPERAWATAN, 2015)
Incomplete documentation can degrade the quality of nursing care. This research was known to conduct relations with the documentation of nursing care nurse. The study design was a descriptive study Analytical approach Cross Sectional. Total number of samples using a sampling technique is a way of collecting a sample based on the overall population of 40 respondents. The results show that good behavior with complete documentation is 20 (66%) and respondents who have good behavior with the documentation is not complete as many as 10 people (33.3%), the behavior is less well with the complete documentation as much as 2 people (20%) and documentation is not complete as many as 8 people (80%). Based on the results of statistical tests, the chi-square p value = 0.025. And with OR 8.000. Conclusions there is a significant relationship with the nurses conduct nursing care documentation. Picture of the behavior of the nurses in the department of CVBC BLU Prof. Dr. R.D Kandou Manado .. Recommendation researchers that the nurses have to make the practice of nursing care documentation, as consideration for improving the appearance of the nurses in the face of the demands of the development of services. Keywords: Documentation of Nursing, nurses Behavior ABSTRAK: Dokumentasi merupakan tanggung jawab dan tugas perawat setelah melakukan intervensi keperawatan. Pendokumentasian yang tidak lengkap dapat menurunkan mutu pelayanan keperawatan. Tujuan penelitian ini adalah diketahui hubungan perilaku perawat dengan pendokumentasian asuhan keperawatan. Desain penelitian ini merupakan penelitian Deskriptif Analitik melalui pendekatan Cross Sectional. Jumlah sampel menggunakan teknik Total sampling yaitu cara pengumpulan sampel berdasarkan keseluruhan populasi 40 responden. Hasil penelitian menunjukkan bahwa perilaku yang baik dengan pendokumentasian lengkap adalah 20 orang (66%) dan responden yang memiliki perilaku baik dengan pendokumentasian tidak lengkap sebanyak 10 orang (33,3%), perilaku kurang baik dengan pendokumentasian lengkap sebanyak 2 orang (20%) dan pendokumentasian yang tidak lengkap sebanyak 8 orang (80%). Berdasarkan hasil uji statistik chi-square maka didapatkan nilai p = 0,025 dan dengan OR 8,000. Simpulan ada hubungan signifikan perilaku perawat dengan pendokumentasian asuhan keperawatan. Gambaran perilaku perawat di CVBC BLU RSUP Prof. Dr. R. D. Kandou Manado.. Rekomendasi peneliti yaitu para perawat harus menjadikan praktek pendokumentasian asuhan keperawatan, sebagai bahan pertimbangan untuk memperbaiki penampilan kerja perawat dalam menghadapi tuntutan perkembangan pelayanan. Kata Kunci : Dokumentasi Asuhan Keperawatan, Perilaku perawat,